2023
DOI: 10.1186/s12889-023-15418-z
|View full text |Cite
|
Sign up to set email alerts
|

STI and HIV testing: examining factors that influence uptake among domestic Australian-born, domestic overseas-born and international tertiary students studying in Australia

Abstract: Objectives Sexual health knowledge among international students in Australia is lower than domestic students, however, little is known about what factors affect the uptake of STI testing, nor if there are differences for overseas-born domestic students. Methods We included sexually active respondents from a survey of university students in Australia (N = 3,075). Multivariate regression and mediation analyses investigated associations of STI and HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Most often, studies explored a vast array of risk factors related to physical health, including bi+ students’ experiences with substance use, drinking, nonmedical prescription drug use, tobacco use, interpersonal violence, sexual violence, sexual harassment, sexual activity, lack of counseling, and weight-related behaviors (Coulter et al, 2016; Duryea et al, 2015; Laska et al, 2015; Li et al, 2018; Lindley et al, 2008; McAleavey et al, 2011; Viohl et al, 2019). Related to outcomes for bi+ populations, Kerr, Ding, and Thompson (2013) and Engstrom et al (2023) found positive outcomes related to sexual health for bi+ people (i.e., higher rates of sexually transmitted infection testing and condom use), whereas Stokłosa et al (2021) found bisexual people to have the riskiest sexual behaviors. Second most common, the literature overviewed an array of risk factors related to mental health, including bi+ students’ greater rates of suicidal ideation, higher diagnoses of mental health concerns (e.g., anxiety, posttraumatic stress disorder, and depression), and lower life satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…Most often, studies explored a vast array of risk factors related to physical health, including bi+ students’ experiences with substance use, drinking, nonmedical prescription drug use, tobacco use, interpersonal violence, sexual violence, sexual harassment, sexual activity, lack of counseling, and weight-related behaviors (Coulter et al, 2016; Duryea et al, 2015; Laska et al, 2015; Li et al, 2018; Lindley et al, 2008; McAleavey et al, 2011; Viohl et al, 2019). Related to outcomes for bi+ populations, Kerr, Ding, and Thompson (2013) and Engstrom et al (2023) found positive outcomes related to sexual health for bi+ people (i.e., higher rates of sexually transmitted infection testing and condom use), whereas Stokłosa et al (2021) found bisexual people to have the riskiest sexual behaviors. Second most common, the literature overviewed an array of risk factors related to mental health, including bi+ students’ greater rates of suicidal ideation, higher diagnoses of mental health concerns (e.g., anxiety, posttraumatic stress disorder, and depression), and lower life satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…Many cultures perceive STIs/HIV as stigmatised conditions 16 18 , including among health professionals 19 and especially where there is intersectional identity 20 22 . FL allows for the development of models that can generalise across different populations, which is crucial for the prediction of STIs and HIV, which disproportionately affects specific groups, such as men who have sex with men (MSM) and people from higher endemic countries 23 .…”
Section: Introductionmentioning
confidence: 99%